2015
DOI: 10.1155/2015/186740
|View full text |Cite
|
Sign up to set email alerts
|

Current Patterns of Management of Advanced Prostate Cancer in Routine Clinical Practice in Spain

Abstract: Objective. To describe urologists' practice patterns when managing patients with advanced prostate cancer (PCa) in Spain. Methods. This was an observational study conducted by 120 urologists using retrospective data of advanced PCa patients attending hospitals and outpatient centers. Results. Urologists evaluated a total of 375 patients (mean age: 75 years; ECOG 0-1: 77%; mean serum PSA levels at study entry: 50.5 ng/Ml). Approximately 50% of patients had bone metastases, and 60.6% experienced pain as the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Use of chemotherapy showed an upward trend after 2005, with a peak in 2009, which could be explained by a slow uptake of docetaxel. On average, chemotherapy use remained low in our cohort, with an overall penetrance of less than 25%, similar to usage rates reported in other observational studies 24,25,42 . The high proportion of patients more than 75 years of age in our population could partly explain the low rate of chemotherapy use overall.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Use of chemotherapy showed an upward trend after 2005, with a peak in 2009, which could be explained by a slow uptake of docetaxel. On average, chemotherapy use remained low in our cohort, with an overall penetrance of less than 25%, similar to usage rates reported in other observational studies 24,25,42 . The high proportion of patients more than 75 years of age in our population could partly explain the low rate of chemotherapy use overall.…”
Section: Discussionsupporting
confidence: 88%
“…Other real-world studies have shown similar patterns, with secondary hormonal therapy being largely used as the only therapeutic intervention during the mcrpc period [40][41][42] . Chemotherapy was prescribed more frequently in younger patients; all other crpc treatments showed a smaller variation with age.…”
Section: Discussionmentioning
confidence: 74%
“…Advances in surgery, radiation, and chemotherapy have increased opportunities to diagnose and manage early-stage prostate cancer ( 15 ). However, there is no consensus currently on the clinical treatment selection protocols for the bone-metastatic PCa patients to extend their life expectancy ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…PC is also a tumor with higher variability in its indication and types of treatment[33]. This is due to a combination of different social, organizational, and clinical factors, which may strongly influence the spatial distribution of PC risk.…”
Section: Discussionmentioning
confidence: 99%